A Gas Cell Based on Hollow-Core Photonic Crystal Fiber (PCF) and Its Application for the Detection of Greenhouse Gas (GHG): Nitrous Oxide (N2O). (29th November 2016) - Valiunas, Jonas K.; Tenuta, Mario; Das, Gautam
Abstract : The authors report the detection of nitrous oxide gas using intracavity fiber laser absorption spectroscopy. A gas cell based on a hollow-core photonic crystal fiber was constructed and used inside a fiber ring laser cavity as an intracavity gas cell. The fiber laser in the 1.55  μ m band was developed using a polarization-maintaining erbium-doped fiber as the gain medium. The wavelength of the laser was selected by a fiber Bragg grating (FBG), and it matches one of the absorption lines of the gas under investigation. The laser wavelength contained multilongitudinal modes, which increases the sensitivity of the detection system. N2 O gas has overtones of the fundamental absorption bands and rovibrational transitions in the 1.55  μ m band. The system was operated at room temperature and was capable of detecting nitrous oxide gas at sub-ppmv concentration level.